PENINGKATAN SPATIAL VISUAL INTELLIGENCE MELALUI KEGIATAN BERMAIN ENGKLEK - Nopiana Nopiana; Ida Nurarida; Suryadi Suryadi (Institut Agama Islam Negeri (IAIN) PALOPO, 2020)
This study aims to describe the process and learning outcomes using media hopscotch in improving children's spatial-visual intelligence. The research model used is the Kemmis and Taggart models with 20 research subjects in Group B PAUD Anak Bangsa, Serang City. The study was conducted in semester 1 of the 2017/2018 Academic Year in October to November 2017 with two cycles. Data collection techniques are done through tests, observations, interviews and documentation studies. The data analysis technique used in this study is a mixed-method, namely qualitative data analysis and quantitative data. Quantitative data analysis was used to find out the percentage increase in children's spatial-visual intelligence after being given an action. Qualitative data analysis is used to describe the results of the study. The results of this study an increase in spatial-visual intelligence in children after participating in learning by using cricket media. Spatial visual intelligence of children in the pre-cycle that is equal to 42.40%. In cycle one there was an increase to 68.65% and increased again in cycle 2 to 85.85% in cycle 2. The process of playing hopscotch had an impact on various aspects of child development such as; physical, cognitive, linguistic and social. The results of this study imply that the process of early childhood learning using a hopscotch playing strategy can be considered as a medium for increasing children's spatial-visual intelligence.